Evaluating Vietnam’s Pre-service English Teacher Education Program for Technology Integration in Education - Thi Kim Anh Vo; Vincent Pang; Lee Kean Wah (2020)
With the rapid development of technology in the world today, the application of technology in education, thus, becomes a matter of great importance. In the English Teacher Competency Framework (ETCF) provided by the Vietnam Ministry of Education and Training, the ability to use technology in education is an essential aspect an English teacher program must include. As revealed from previous studies, English teachers’ ability to integrate technology in education is weak as they have not been provided adequate opportunities to learn and integrate technology in education in their pre-service teacher education programs. This paper reports on part of findings of a case study conducted in Vietnam. The research adopted a qualitative approach with the in-depth interview as the instrument. Research participants consisted of experienced lecturers involved in designing the program and student teachers. Findings revealed that the program was not effective in educating student teachers in the methods of using technology in teaching. The reasons for such inadequacy were lack of knowledge of technology integration in language teaching, poor facilities, and low ICT capacity. Integrating technology in the curriculum is suggested for developing student teachers’ ability to apply technology in education.